2011
DOI: 10.1021/bm201564a
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Whiskers: An Overview

Abstract: Chitin is the second most abundant semicrystalline polysaccharide. Like cellulose, the amorphous domains of chitin can also be removed under certain conditions such as acidolysis to give rise to crystallites in nanoscale, which are the so-called chitin nanocrystals or chitin whiskers (CHWs). CHW together with other organic nanoparticles such as cellulose whisker (CW) and starch nanocrystal show many advantages over traditional inorganic nanoparticles such as easy availability, nontoxicity, biodegradability, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
282
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(290 citation statements)
references
References 127 publications
(278 reference statements)
8
282
0
Order By: Relevance
“…Typical polysaccharides that acquire a polycrystalline character during their biosynthesis are starch 43 , cellulose 44,45 and chitin. 46 In cellulose and chitin for instance, acid hydrolysis of the amorphous regions results in fabrication of a new materials that consist of aggregates of cellulose or chitin crystals at various length scales. These materials find applications in food and pharmaceutical industries as fat substitutes, texture modifiers, tablet binders or additives that reinforce polymer composites.…”
Section: Figure X3 Around Herementioning
confidence: 99%
“…Typical polysaccharides that acquire a polycrystalline character during their biosynthesis are starch 43 , cellulose 44,45 and chitin. 46 In cellulose and chitin for instance, acid hydrolysis of the amorphous regions results in fabrication of a new materials that consist of aggregates of cellulose or chitin crystals at various length scales. These materials find applications in food and pharmaceutical industries as fat substitutes, texture modifiers, tablet binders or additives that reinforce polymer composites.…”
Section: Figure X3 Around Herementioning
confidence: 99%
“…Two disaccharide motifs comprise the orthorhombic unit cell of -chitin [2,3], the polymer chain being oriented along the c-axis which is the fiber axis. In marine creatures the crystallite width and length ranges are 10-50 nm and 150-2200 nm [4], respectively, and depend on the source of α-chitin. However, in insects the width is only around 2-3 nm [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that incorporating a small amount (1-10 %) of these nanocrystals into polymers can induce vast improvement in properties [1,13]. The properties enhancement can be realized by uniform dispersion of the nanocrystals in polymer matrix via solution mixing or melt mixing [14]. In these composite systems, interfacial interactions between the matrix and the filler are critical.…”
Section: Introductionmentioning
confidence: 99%